Occult Hepatitis B virus infection in previously screened, blood donors in Ile-Ife, Nigeria: implications for blood transfusion and stem cell transplantation. Issue 1 (December 2016) - Olotu, Amadin; Oyelese, Adesola; Salawu, Lateef; Audu, Rosemary; Okwuraiwe, Azuka; Aboderin, Aaron
Abstract Background Hepatitis B virus (HBV) transmission through blood transfusion is reduced by screening for hepatitis B surface antigen (HBsAg). However this method cannot detect the presence of occult hepatitis B virus infection. This study sought to determine the prevalence of occult hepatitis B virus infection among blood donors in Ile-Ife, Nigeria. For the first time in Nigeria we employed an automated real-time PCR- method to investigate the prevalence of occult HBV in blood donors. Methods Blood donors screened with HBsAg immunochromatographic rapid test kits at the blood transfusion units of two hospitals and found to be negative were recruited into the study. Questionnaires to elicit risk factors for HBV infection were administered and then 10 ml of blood was collected from each donor. Plasma samples obtained from these HBsAg negative blood donors were screened again for HBsAg using an enzyme-linked immunosorbent assay (ELISA) method, and those found negative were screened for the presence of total antibody to the HBV core antigen (anti-HBc) using ELISA method. Those positive to anti-HBc were then tested for HBV DNA, using an automated real-time PCR method. Results Five hundred and seven blood donors found HBsAg negative by immunochromatographic rapid test kits at both blood transfusion units, were tested for HBsAg using ELISA and 5 (1 %) were HBsAg positive. The 502 found negative were tested for anti-HBc and 354 (70.5 %) were found positive implying previous exposure to HBV and 19 (5.4 %) of the 354 anti-HBc positive had HBV DNA signifying occult HBV infection. No risk factors were found to be associated with the presence of HBV DNA among those who tested positive. Conclusion Occult HBV infection exists in blood donors in Ile-Ife, Nigeria and the use of HBsAg alone for screening prospective donors will not eliminate the risk of HBV transmission in blood transfusion or stem cell transplantation.